Contaminated operating theatre foot wears: a potential source of healthcare associated infections in a northern Nigerian hospital - Nwankwo, Emmanuel Onwubiko; Akande, Azeez Oyebanji (International Journal of Infection Control, 2015)
Operating theatre foot wears (OTFWs) contaminated with potential pathogens are increasingly recognized as possible sources of healthcare associated infections (HCAIs). This study was undertaken to determine the rate of microbial contamination of OTFWs with potential nosocomial pathogens.Sterile cotton wool – tipped swabs momentarily immersed in physiological saline were used to collect samples from parts(i.e. surface and soles) of the OTFWs regularly worn by the operating theater personnel at Murtala Mohammed Specialist Hospital (MMSH), Kano between January and June, 2010. These were cultured by standard procedures and examined for bacterial and fungal growth. Presence of human haemoglobin on non visible blood stained foot wears was confirmed with rapid chromatological immunoassay. Bacterial and fungal isolates were identified by standard microbiological methods Out of a total of 136 pieces of foot wears examined, 56(41.2%) were found with no visible blood stain while blood stain was detected on 80(58.8%). However, greater number 92(68.0%) of foot wears were found to carry blood stain when chemical analysis was adapted.Streptococcus spp. and Staphylococcus epidermidis were most frequently isolated. The findings from this study could be used to adapt appropriate preventive measures in the theater to limit transmission of potential pathogens from HCAIs.